Hope for Africa : selected speeches of Olusegun Obasanjo - Obasanjo, Olusegun (Abeokuta, Ogun State, Nigeria : ALF Publications, 1993)
The book contains a list of speeches concerning African, its population, environment, climate, past and present, development, wars among others.
Includes index.
nmn, 01/08/18, ijb 06/02/2019
Loans
Keywords: Politics and government - Speeches; Speeches - Obasanjo; Africa